1999
DOI: 10.1055/s-0037-1614550
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Low-Molecular-Weight Heparin in Pregnancy: A Systematic Review

Abstract: SummaryUnfractionated heparin (UFH) remains the anticoagulant of choice during pregnancy. Low-molecular-weight heparins (LMWH) are an attractive alternative to UFH due to their logistic advantages and their association with a lower incidence of osteoporosis and HIT. We reviewed all published clinical reports concerning the use of LMWH during pregnancy. In addition, participants of an international interest group contributed a cohort of pregnant women treated with LMWH. Pregnancies were divided into two groups;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
280
3
28

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 508 publications
(320 citation statements)
references
References 34 publications
9
280
3
28
Order By: Relevance
“…Low molecular weight heparin has the advantage over unfractionated heparin of a longer plasma half-life and a more predictable dose response and therefore the potential for once daily administration. Furthermore, low molecular weight heparin causes less heparininduced thrombocytopenia and heparin-induced osteoporosis (62,64). Given these advantages, we prefer low molecular weight heparin, although this approach is more expensive.…”
Section: Recommendationsmentioning
confidence: 99%
“…Low molecular weight heparin has the advantage over unfractionated heparin of a longer plasma half-life and a more predictable dose response and therefore the potential for once daily administration. Furthermore, low molecular weight heparin causes less heparininduced thrombocytopenia and heparin-induced osteoporosis (62,64). Given these advantages, we prefer low molecular weight heparin, although this approach is more expensive.…”
Section: Recommendationsmentioning
confidence: 99%
“…Dolitzky et al [2] reported high efficacy and few complications of enoxaparin in patients with recurrent pregnancy loss. Sanson et al [3] reported low molecular weight heparins as an attractive alternative to unfractionated heparin due to their logistic advantages and their association with a lower incidence of osteoporosis and thrombocytopenia.…”
Section: Discussionmentioning
confidence: 99%
“…Low molecular weight heparin therapy has widespread use during pregnancy for various indications. Concerns about its safety in pregnancy have been raised and there are various studies to support its safety on maternal and fetal outcome [1][2][3]. There are no such studies from the Indian population; hence, we tried to evaluate safety and efficacy of low molecular weight heparin given during pregnancy for various indications over a period of 3 years in our hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies are of low quality because of their historic controls. Although LMWH is widely used in pregnancy for prophylaxis of venous thromboembolism and although relevant adverse reactions are rare [12], its application in women with fetal loss requires thorough information on the risk-benefit ratio.There is much discussion on the impact of thrombophilic factors as risk determinants of pregnancy complications including recurrent pregnancy loss or pre-eclampsia [10]. In contrast to venous thromboembolism, the data are more conflicting, particularly in women with early fetal loss.…”
mentioning
confidence: 99%
“…Most of these studies are of low quality because of their historic controls. Although LMWH is widely used in pregnancy for prophylaxis of venous thromboembolism and although relevant adverse reactions are rare [12], its application in women with fetal loss requires thorough information on the risk-benefit ratio.…”
mentioning
confidence: 99%